Marketing digital y el posicionamiento de la marca Sporade de la Empresa Aje Group en Guayaquil - Sánchez Veliz, Marlon Rodrigo (2023)
Currently there are many isotonic or rehydration drinks in the market in the city of Guayaquil that offer many benefits to the consumer when looking for a product that restores the minerals that were consumed in some physical activity to the body. The multinational Aje Group is a company of Peruvian origin that has a presence in 23 countries, both in Latin America, Asia and Africa, it was founded in 1988 in the capital Lima. In recent years it has been possible to observe that the competent brands of isotonic drinks have improved their positioning, which has displaced the Sporade brand from its location in the market, thus causing consumers to opt for an isotonic drink when they require an isotonic drink. brand as Powerade or Gatorade, rather than Sporade. Among the reasons that were observed is the limited communication strategies in digital media that the multinational makes to expose the benefits of the isotonic drink that they offer through the Sporade brand. The present investigation will have a deductive and inductive methodology. On the deductive side, a type of thinking will be used that goes from a more general and logical reasoning, based on laws or principles, to a concrete fact.